Lenalidomide maintenance after second autologous stem cell transplant improves overall survival in multiple myeloma. Issue 8 (2nd July 2020) - Modi, Dipenkumar; Chi, Jie; Kim, Seongho; Ayash, Lois; Alavi, Asif; Kin, Andrew; Ratanatharathorn, Voravit; Uberti, Joseph P.; Deol, Abhinav
Abstract: Maintenance therapy after first autologous transplant (autoSCT) improves progression-free survival (PFS) and overall survival (OS) in multiple myeloma (MM). However, efficacy of maintenance therapy after second autoSCT is unknown. We retrospectively evaluated outcomes of 111 adult MM patients who underwent second autoSCT between January 2000 and December 2018. Lenalidomide up to 15 mg daily or subcutaneous bortezomib 1.3 mg/m 2 every 2 weeks was considered maintenance therapy. Outcomes were compared among three groups: no-maintenance ( n = 73), lenalidomide ( n = 23), and bortezomib maintenance ( n = 15). At a median follow-up of 58 months from second autoSCT for survival, 3-year PFS and OS for no-maintenance, lenalidomide, and bortezomib maintenance were 11.2%, 29.9%, and 0%, respectively; and 58.5%, 83.3%, and 67.5% respectively. Lenalidomide maintenance was associated with improved PFS (HR 0.46, p = 0.009) and OS (HR 0.25, p = 0.009) compared to no-maintenance. Lenalidomide maintenance therapy after second autoSCT appears to prolong PFS and OS.